The Effectiveness of Franchise Strategy in Marketing Mixue Products - Nurwahyuni, Dwi; Fransiska Eka Maharani; Salza Ayu Ramadhana; Rusdi Hidayat; Indah Respati Kusumasari (Publikasi Inspirasi Indonesia, 2024)
The marketing strategy used by each company is different, this depends on the policy taken by the owner or leader of the company. This article will discuss the franchise strategy used by Mixue in marketing their products so that it can become one of the well-known ice cream and tea companies in Indonesia. Using a literature review, we assessed whether the franchise strategy implemented by Mixue was effective in marketing their products. SWOT analysis is also applied so that the results of the analysis are really concrete so that the franchise strategy can be implemented by local Indonesian entrepreneurs. Mixue has not only succeeded in attracting franchisees to participate in their business development, but they also provide training, operational guidelines and appropriate strategies so that each outlet built succeeds in bringing profits to the brand. In addition, Mixue also continues to innovate with their products so that the products sold remain relevant in the market and in accordance with consumer demand. Not only maintaining quality and continuing to develop innovation, Mixue also conducts slick marketing through social media. Their collaborations with influencers are mostly successful in bringing new consumers to try the products offered. In addition, this article also discusses the weaknesses of the franchise strategy carried out by Mixue so that it can be considered by other entrepreneurs who want to adopt the same system. In conclusion, the franchise strategy carried out by Mixue has succeeded in keeping this company alive in the market. They also succeeded in proving that this business is not only profitable for franchisors but also franchisees, so that more and more business partners are involved in the development of Mixue products in the future.